A comprehensive literature study on the effect of cannabis use on cognition and aggressiveness, including a small study to explore these variables - Fanshawe, Nigel Charles (Department of Psychiatry and Mental Health, 2017)
Twenty seven consecutive black male patients who were admitted as acute admissions to FEH were examined in this thesis. The following demographic information characterized the sample group. a) Age: Bimodal distribution with peaks at 21-25 years and 31-35 years. Five patients were older than 35 years. b) Marital Status: In the sample. 59.2% were single. 11.1 % married and 29.6% the marital status was unknown. c) Number of Children: In the sample. 75% did not know how many children they had. Numbers ranged from no children (14.3%) to 2 children (7.1% of the sample). d) Employment Status: In the sample 81 .1 % were unemployed. e) Level of Schooling: In one third of cases, level of schooling was unknown. Most men did reach secondary level of education.